2020
DOI: 10.1002/mrm.28612
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hyperpolarized 13C and non‐hyperpolarized deuterium MRI approaches for imaging cerebral glucose metabolism at 4.7 T

Abstract: The purpose of this study was to directly compare two isotopic metabolic imaging approaches, hyperpolarized (HP) 13 C MRI and deuterium metabolic imaging (DMI), for imaging specific closely related segments of cerebral glucose metabolism at 4.7 T. Methods: Comparative HP-13 C and DMI neuroimaging experiments were conducted consecutively in normal rats during the same scanning session. Localized conversions of [1-13 C]pyruvate and [6,6-2 H 2 ]glucose to their respective downstream metabolic products were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…Moreover, its chemical shift spread enables an easier signal resolution. However, the longer acquisition time of DMI allows to observe not only the lactate but also Glx (glutamine and glutamate) production, thus creating metabolic map for both oxidative and non-oxidative pathways of glucose metabolism [ 61 ]. A variety of other analogous methods have been used relying on bioconversion of an administered probe including hyperpolarized 15 N MRI, as well as studies at thermal equilibrium using 13 C, 15 N, 19 F, and 31 P [ 62 , 63 , 64 , 65 , 66 ].…”
Section: Dmi-companion Metabolic Imaging Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, its chemical shift spread enables an easier signal resolution. However, the longer acquisition time of DMI allows to observe not only the lactate but also Glx (glutamine and glutamate) production, thus creating metabolic map for both oxidative and non-oxidative pathways of glucose metabolism [ 61 ]. A variety of other analogous methods have been used relying on bioconversion of an administered probe including hyperpolarized 15 N MRI, as well as studies at thermal equilibrium using 13 C, 15 N, 19 F, and 31 P [ 62 , 63 , 64 , 65 , 66 ].…”
Section: Dmi-companion Metabolic Imaging Toolsmentioning
confidence: 99%
“…Straathof et al showed glucose metabolism after ischemic stroke in rats by presenting a significant increase in lactate formation in the diseased animals [ 98 ]. Furthermore, a recent publication compered DMI and HP [1- 13 C] pyruvate in imaging of cerebral metabolism, showing that they are both feasible methods at 4.7 T [ 61 ]. An alternate approach, described recently in Mahar et al, was to assess cerebral glucose metabolism by administering [ 2 H 7 ] glucose by looking at the HDO as the metabolic product, bypassing the need for lower resonance products such as lactate and Glx and showing that HDO can indeed serve as a biomarker of [ 2 H 7 ] glucose, lactate, and Glx metabolism [ 99 ].…”
Section: Probes For Dmimentioning
confidence: 99%
“…MR spectroscopy (MRS) and spectroscopic imaging (MRSI), following the administration of deuterated metabolites, have recently been introduced and applied to image tissue metabolism 25–34 . Exogenously administered 2 H 6,6′ ‐glucose was found to originate 2 H 4,4′ ‐glutamate and 2 H 4,4′ ‐glutamine peaks in healthy brains, as well as a 2 H 3,3′ ‐lactate signature in tumors; a significant production of 2 H‐water was also detected in all the tissues.…”
Section: Introductionmentioning
confidence: 99%
“…However, PET imaging has disadvantages such as (1) using radioactive contrast agents which risk human health; (2) having limited applications for expectant mothers, children, and infants; (3) labeling agents with 18 F (e.g., 2‐ 18 F‐fluoro‐2‐deoxy‐ d ‐glucose, 18 FDG) as being unable to participate in downstream reactions, thus not being able to provide intact and complete metabolic information. Hyperpolarized 13 C magnetic resonance imaging (MRI) performs satisfactorily in both signal‐to‐noise ratios (SNRs) and spatial resolution [Merritt et al, 2007; von Morze et al, 2021], but the demanding polarization process and its short half‐life restrict the applications. A technique called deuterium metabolic imaging (DMI), which is based on deuterium magnetic resonance spectroscopy (MRS), has been developed recently to overcome these disadvantages [De Feyter et al, 2018, 2021; De Graaf et al, 2021; Hesse et al, 2021; Kreis et al, 2020; Lu et al, 2017].…”
Section: Introductionmentioning
confidence: 99%